An Existence Result for Henstock-Kurzweil-Stieltjes-⋄-Double Integral of Interval-Valued Functions on Time Scales - Afariogun, David Adebisi; Mogbademu, Adesanmi Alao (Journal of Nepal Mathematical Society, 2021)
We employ the concept of interval-valued functions to state and prove an existence result for the Henstock-Kurzweil-Stieltjes-⋄-double integral on time scales.